Occupational therapy interventions for community re-integration of mental health care users with severe mental illness in low- and middle-income countries: a scoping review - Mabuza, Lozinyanga (Division of Occupational Therapy, 2025)
Objectives: To describe occupational therapy interventions for the community re-integration of mental health care users (MHCUs) and the factors that influence this process in low- and middle-income countries (LMICs) Introduction: Mental health issues affect a large portion of the global population, with severe mental illness (SMI) contributing significantly to the global disease burden particularly in LMICs where access to care is limited. Community re-integration for MHCUs is a serious challenge, often leading to the revolving door phenomenon. Community-based mental health care models aim to improve patient outcomes and support re-integration. Occupational therapy plays a significant role in this recovery process; however, the evidence is scattered, with no existing summary of literature for LMICs. Inclusion criteria: This scoping review included studies from 2002 to 2023 that reported occupational therapy interventions for community re-integration of previously institutionalised MHCUs with severe mental illness. The studies were selected from LMICs and included various research designs, theoretical articles, and grey literature. Methods: A search strategy was developed with a subject librarian and PubMed, Scopus, EBSCOHost (CINAHL, Africa-Wide Information, APA PsycArticles, and APA PsycInfo), OATD.org, and WorldCat were searched. The search was conducted from January to February 2023. Two reviewers independently screened eligible studies using the Rayyan web application. The data were extracted using a modified JBI data-charting tool and organised in a table using two organising categories. Data were coded by similar factors, summarised, and reported descriptively. Results: Of the 287 articles identified in the searches, 10 met the inclusion criteria. Sources were from South Africa (5 sources), India (2 sources), China (1 source) and Brazil (1 source), and were mostly qualitative and based in community practice sites. Nine distinct occupational therapy interventions were identified – actuality, community living skills and support, counselling, home visits, life skills, leisure, psychoeducation, self-care, and vocational rehabilitation. The six contributing factors included community-based rehabilitation principles, psychosocial strategies, assessment and outcome measures, the concept of recovery, occupational therapy-led programmes and elements of the interventions. Conclusion: Interventions that aligned with occupational therapy principles that were culturally adapted were particularly effective in facilitating MHCUs' re-integration in LMICs Adapting outcome measures and re-integration indicators to the local context is crucial.